2006
DOI: 10.1002/smll.200600297
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Ferroelectricity in Quasi‐Zero‐Dimensional Barium Titanate Nanoparticles

Abstract: Understanding the behavior of ferroelectric response in zero-dimensional systems, that is, under three-dimensional quantum confinement, is an important task from the technological point of view, which might lead to further miniaturization of electrical devices. Evidently, carrying out direct electrical measurements on ideal zero-dimensional nanoparticles is an extremely nontrivial process, although several experimental reports employing indirect methods have been published. However, the use of recently develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The wire is assumed to extend indefinitely out of the model plane, such that plane strain and plane electric field conditions apply. Minimum cross-sectional widths of 20nm were considered, noting that ferroelectricity has been observed in BaTiO3 structures from a few nanometers in size upwards [34][35][36]. The wire is assumed to be simply supported, with traction free surfaces.…”
Section: Polarization Flux Closures In the Form Of Bundles Of 90mentioning
confidence: 99%
“…The wire is assumed to extend indefinitely out of the model plane, such that plane strain and plane electric field conditions apply. Minimum cross-sectional widths of 20nm were considered, noting that ferroelectricity has been observed in BaTiO3 structures from a few nanometers in size upwards [34][35][36]. The wire is assumed to be simply supported, with traction free surfaces.…”
Section: Polarization Flux Closures In the Form Of Bundles Of 90mentioning
confidence: 99%
“…4 The feasibility of these ferroelectric ceramic based, miniaturized technologies depends on the scaling of the macroscopic functional properties with size. 8 However, this does not guarantee the functionality of the ferroelectric ceramic nanostructured elements that depends on how macroscopic properties such as polarization switching and retain, linear polarizability, and piezoelectricity scale with the decrease in grain size. 5 There are now solid evidences that ferroelectricity persists in nanoscale films, 6 wires, 7 and particles.…”
Section: Macroscopic Ferroelectricity and Piezoelectricity In Nanostrmentioning
confidence: 99%
“…Ferroelectricity is a cooperative phenomenon, and it was long thought that a minimum volume was necessary to sustain the spontaneous polarization; this raises the existence of a fundamental size limit below which ferroelectricity vanishes 11. 12 First‐principles calculations and experimental studies on nanostructured films,1316 wires,17, 18 particles,19, 20 and ceramics21 have shown that ferroelectricity persists at the nanoscale and thus, that the downscaling of ferroelectric‐based piezoelectric technologies is feasible. However, most studies focused on prototype, simple perovskites, such as BaTiO 3 , PbTiO 3 , or tetragonal Pb(Zr,Ti)O 3 , whereas results on high‐piezoelectric‐coefficient morphotropic‐phase‐boundary (MPB) materials are scarce 22.…”
Section: Introductionmentioning
confidence: 99%